Business continuity, a constant issue for managers and auditors - BRAGA, Viorica (Annals of Spiru Haret University. Economic Series, 2010)
The crisis of credits and its effects upon all companies, make the assumption of activity continuity be not anymore a pre-established conclusion. The major cash issues, affecting the banks, insurance companies, retailers, car manufacturers and all companies regardless of their activity, prove that keeping the business continuity, i.e. having enough funds for compliance with an obligation to be able to reach maturity at least twelve months after the balance sheet date is now a real problem for many companies. Likewise, we are paying attention to the topic and to the increasing number of insolvencies at the national, European and international levels.